National and regional aspects of formation of physical culture and recreation environment in educational institutions of the Republic of Tatarstan - Manurov, Ilgiz M.; Kalmanovich, Vladimir L. (Физическое воспитание и студенческий спорт)
Creation of modern professional, focused on meeting the needs of the student youth physical culture and recreation environment of the university will create opportunities for solving problems aimed at the development of student sports, improving the quality of life in general and the level of health in particular. In our work, we applied such methods as study and comparative analysis of pedagogical and methodological literature; systematic analysis of legal documents; generalization of the experience of pedagogical practice; questionnaires; methods of mathematical statistics and experimental methods. Physical culture and wellness environment of the university has a huge value potential and great opportunities in the field of training organization and education of students, formation of general culture, development of socially significant qualities and personal attitude to health care as a value. Considering the processes of health saving as a pedagogical unit, we believe it is necessary to build the process of education and self-education in a fundamentally different way, where the process of valeological education of a student in unity with professional valeological training of teaching staff of the university can become innovative. The sports and recreation environment is a broad sphere imbued with the values of humanity and an abundance of educational opportunities. In such atmosphere, the desire for independent search for knowledge and methods of self-realization is cultivated.